From Tradition to Academia: The Institutionalization of Silat in Malaysia (2014–2024) - Mohamad Nizam Mohamed Shapie; Mohamad Rahizam Abdul Rahim; Nagoor Meera Abdullah; Jamiaton Kusrin; Ardo Okilanda; Nurul Ihsan (International Martial Arts and Culture Journal, 2026)
This study explores how Silat or Silat Melayu, long rooted in cultural tradition and community practice, has gradually evolved into a recognised academic discipline in Malaysia between 2014 and 2024. Led by Universiti Teknologi MARA (UiTM) and supported by national organisations such as PASSMAL and PESONA, this transformation reflects a deliberate effort to bring together heritage, education, and science within a structured academic framework. Using a qualitative multi-source approach, the study draws on 47 publications, expert insights, and international case comparisons to understand this development. The findings reveal a clear three-phase progression: early efforts focused on building basic scientific evidence, followed by a phase of training innovation, curriculum integration, and athlete safety, and more recently, a shift towards international collaboration and interdisciplinary research through platforms such as AIRBORNE. Across this journey, five key areas have shaped Silat scholarship: performance science, training and conditioning, curriculum development, injury prevention and recovery, and the preservation of cultural identity. The integration of technologies such as motion analysis has further strengthened coaching practices and athlete welfare, while global networks like IMACSSS and UNESCO-ICM have expanded Silat’s academic reach beyond Malaysia. At the same time, this rapid development brings important challenges, particularly in maintaining cultural authenticity and ensuring balanced global partnerships. Overall, the study shows that Malaysia’s experience offers a practical and forward-looking model for integrating indigenous martial arts into higher education. By carefully balancing tradition with scientific advancement, Silat demonstrates how cultural heritage can remain relevant, respected, and globally engaged in the modern academic landscape.